Investigation of the effects of acid rain on the deterioration of cement concrete using accelerated tests established in laboratory - Shaodong Xie; Qi, Li; Zhou, Ding (Atmospheric Environment, 2004)
Deterioration of cement concrete specimens caused by simulated acid rain was investigated by laboratory tests. Before and after cement concrete specimens were exposed to simulated acid rain, the neutralized depth, the compressive strength and the chemical compositions in the hardened cement paste were measured. The mineralogical composition of the concrete specimens was analyzed with XRD. The results lead to the following conclusions: the neutralized depth of the concrete specimens of all experiments can be described as a power function of exposure duration, CaO loss and the reduction rate of strength increased with H+and decreased with SO42− concentration in simulated acid rain. The original mineral compounds such as [Na K]AlSi3O8 and [Ca Na][SiAl]4O8 in the hardened cement paste are converted to CaSO4·2H2O, CaAl2Si2O8 and Ca3Al6O12·CaSO4. And these are larger in volume so that the reaction with SO42− ions result in volume expansion and strength decrease. The reduction rate of strength has a binary linear relation to the CaO loss rate and the ratio of SO3 content to CaO content in the hardened cement paste. So the deterioration of acid rain on the concrete specimen is caused by both H+ dissolution and SO42−expansion.